The explosion of supernova 2011fe in the frame of the core-degenerate scenario - Soker, Noam (2013)
We argue that the properties of the Type Ia supernova (SN Ia) SN 2011fe can be best explained within the frame of the core-degenerate (CD) scenario. In the CD scenario, a white dwarf (WD) merges with the core of an asymptotic giant branch (AGB) star and forms a rapidly rotating WD, with a mass close to and above the critical mass for explosion. Rapid rotation prevents immediate collapse and/or explosion. Spinning down over a time of 0-1010 yr brings theWD to explosion. A very long delayed explosion to post-crystallization phase, which lasts for about 2 × 109 yr, leads to the formation of a highly carbon-enriched outer layer. This can account for the carbon-rich composition of the fastest-moving ejecta of SN 2011fe. In reaching the conclusion that the CD scenario best explains the observed properties of SN 2011fe, we consider both its specific properties, like a very compact exploding object and carbon-rich composition of the fastest-moving ejecta, and the general properties of SNe Ia.